Impacto da radiação solar sobre a aptidão e capacidade locomotora de girinos - Santos, Caroline Peripolli dos (2016)
On the last decades, amphibian populations have been suffering a global decline, and different factors can be related to this process. Parallel observations between the decrease of stratospheric ozone concentration in the late 1970s and amphibian decline in early 1980s aroused interest to study the possible association among increased incidence of ultraviolet radiation (UV) and amphibian decline. The UV radiation has important biological impact on living organisms due to their ability to induce lesions in the DNA molecule, which may result in the induction of mutations or cell death. Photoreactivation is an important DNA repair mechanism that promotes the reversal of UV-induced DNA damage by photolyase enzymes after the absorption of UVA and visible light photons. In this study, we evaluated the biolocial effects of UVB and UVA through morphological, histological, locomotor and survival of Hypsiboas pulchellus (Anura: Hylidae) tadpoles. Tadpoles kept in the laboratory were submitted to acute and chronic treatments, composed of different doses of UVB and UVA exposures. The results of survival curves indicate that the H. pulchellus is very sensitive to UVB radiation comparative to UVA. However, despite the high tadpole survival after UVA, they showed serious malformations after metamorphosis. Tadpoles body weight also suffered influence of different UV radiation doses, however the body length was bit affected. The locomotor capacity (horizontal and vertical speed) of UVB-exposed tadpoles has been significantly changed. In addition, UVB radiation had severe impact on the skin (stratum corneum) and mouth (rows of teeth and jaw sheaths) keratin structures of tadpoles, indicating that these should be important impacts of solar UV radiation in reducing the performance of these organisms. In parallel, it was also possible to observe the extreme importance of activation of photolyases for the repair of DNA damage after treatment with UVB but not UVA. Therefore, in this study, we present a wide characterization of the biological effects of solar UVB and UVA on the performance of H. pulchellus tadpoles.